Delineation and Mapping of Riverine Wetlands in the Middle Ganga River using Geospatial Technology - Zeeshan Ali, Sk.; Guha, Srijani; Mani, Ashish; Menon, Ambika Nandini R.; Barthwal, Shivani; Badola, Ruchi; Hussain, Syed Ainul (Indian Forester, 2025)
The wetlands are natural sink of pollutants and provides ecosystem services worldwide. Rapidly declining water resources is a global concern, underscored by international conventions such as the Ramsar Convention on Wetlands. The riverine wetlands are located at river floodplain and seasonally connected with the main stem river. Delineation and mapping of these wetlands are important to visualize their distribution pattern. We conducted the study in the middle Ganga River using geospatial techniques to delineate and map riverine wetlands. Result shows the wetlands are distributed along the active river channel in the Ganga River floodplain, which are seasonally connected with the Ganga River in monsoon. The wetlands are replenished with nutrients during fluvial connectivity. Wetlands are delineated and mapped (n=788) using Landsat 8 OLI satellite image by Modified Normalized Difference Water Index (MNDWI) by separating the water and land area using green and short wave infrared spectral bands of satellite image. These wetlands are home to various aquatic and water associated avian species, amphibian and reptiles. Conservation measures for these riverine wetlands are essential for sustainability of wetland ecosystem and wetland inhabiting flora and fauna and rejuvenation of the Ganga River system. Some of the wetlands are declared as protected area and Ramsar conservation sites, whereas more wetlands are need to be conserved under national conservation authority to conserve their natural integrity and to protect its biodiversity. This study provides insights and framework for freshwater habitat management for aquatic biodiversity.